Latar Belakang, Potensi dan Dampak Balanced Scorecard Dalam Pengukuran Financial - Amelia Setiawan (Bina Ekonomi, 2001)
Financial accounting model that we used emphasizes on financial measure. Rapid technological innovation especially in information technology requires new capabilities for competitive success. The need to build long-range competitive capabilities and the fact about historical-cost financial accounting created a new tool for management in financial measure: the balanced scorecard. The Balanced Scorecard emphasizes that financial and nonfinancial measure must be part of information system for employees at all level of the organization.